Bridging Liver Transplantation in the Treatment of Intestinal Failure Associated Liver Disease in Infants-A Bridge Too Far? - Abubakar Sharif; Khalid Sharif; Darius F. Mirza; Girish L. Gupte (MDPI AG, 2022)
Infants with intestinal failure associated liver disease (IFALD) requiring liver and bowel transplant have a high mortality on the transplant waiting list due to the scarcity of the size-matched donor organs. Bridging liver transplantation has been used to allow the children to grow to a reasonable size so that a combined liver and small bowel transplant could be performed in the future. We report on two children with irreversible intestinal failure (ultra-short bowel syndrome secondary to gastroschisis and microvillous inclusion disease) with IFALD who underwent bridging liver transplantation at our institution. Both patients made a good recovery from their initial surgery. One patient died 6 months following surgery from generalized sepsis, and the other patient survived in good condition to undergo a combined liver and small bowel transplant but died a few days post-transplant. In the current era of scarcity of donor organs, this raises an ethical dilemma for the team involved regarding appropriate utilisation of a scarce resource.